EMBODIMENT, IDENTITY FORMATION AND MISSIONAL LEADERSHIP: ROOTS OF THEORY AND PRACTICE IN THEOLOGICAL EDUCATION - J. Barentsen (Acta Theologica)
The relationship between theory and practice refracts differently in my journey in practical theology, during which I moved from deductive to inductive approaches, and from New Testament studies to practical ecclesiology and religious leadership. This article offers a conceptual analysis of the theory/practice relationship through the lens of three major concepts that have marked my academic journey. Embodiment focuses on our bodies as the empirical and spiritual locus of human experience and knowledge. Practices and theories emerge in our bodily engagements with the world and one another. Identity formation is the focus of learning processes that shape selves to create personal, social and religious identities that enable us to engage our social and religious worlds. Missional leadership is intent on discerning divine involvement in embodied faith practices in neighbourhoods, communities and contexts. The argument culminates in an agenda for theological education for the next decade.